Modelling of solid bodies in dissipative particle dynamics - Mai-Duy, N. (2014)
Particle-Based Methods III: Fundamentals and Applications - Proceedings of the 3rd International Conference on Particle-based MethodsFundamentals and Applications, Particles 2013